Study of pesticide side-effects in winter wheat trials - Petróczi, István Mihály; Matuz, János; Kótai, Csaba (Acta Biologica Szegediensis, 2002)
Wide range of wheat varieties were investigated in field trials and greenhouse, to study the different side-effects of herbicides and fungicides. Side-effects of seed dressings were more characterized on the wheat varieties with a short vegetation period, than for those with a longer one, both in the intensity of germination, dry matter accumulation and yield production. The depressive side-effects of herbicides were also in a close connection with the genotypes. Spraying with triazole fungicides increased the yield and inhibited the senescence of flag leaf with a protracted chlorophyl retention.